Grenville Goodwin Among the Western Apache Letters from the Field - Opler, Morris E. (University of Arizona Press, 2019)
Grenville Goodwin was one of the leading field anthropologists during a crucial period in American Indian research-the 1930s. His letters from the field provide original source material on Western Apache beliefs and customs. They also reveal the attitudes and methods which made him so effective in his work. A dedicated and thorough ethnographer, Goodwin became familiar with every aspect of Western Apache culture. During this same period, Morris Opler was studying the Chiricahua and Mescalero Apache in New Mexico. In order to exchange information about their studies, Goodwin and Opler began corresponding. Both men were convinced that a long-overdue, systematic comparison of Apachean cultures would yield significant results.